Perceptions on the effect of small electric fans on comfort inside bed nets in southern Ghana: a qualitative study. (December 2016) - Jaeger, Mulako; Briët, Olivier; Keating, Joseph; Ahorlu, Collins; Yukich, Joshua; Oppong, Samuel; Nardini, Peter; Pfeiffer, Constanze
Abstract Background Long-lasting insecticidal nets (LLINs) are known to be highly effective in reducing malaria transmission, morbidity and mortality. However, among those owning an LLIN, use rates are often suboptimal. A reported barrier to bed net use is discomfort due to heat. This qualitative study was part of a larger evaluation conducted in communities without electricity in rural Ghana to assess whether 0.8 W solar powered net fans can increase net use. Methods Twenty-three key informant interviews with household heads in the study communities in Shai-Osudoku District, southern Ghana, were conducted from July to August 2015. The purpose of the interviews was to obtain insight into perceptions of participants about the net fan system in relation to LLIN use. Results While all study participants reported using LLINs, with mosquito nuisance prevention as the prime motivation, heat was also mentioned as a key barrier to net use. Respondents appreciated the net fans because they improved comfort inside bed nets. The LED light on the fan stand became the main source of light at night and positively influenced the perception of the intervention as a whole. Conclusion The general acceptance of the net fan system by the study participants highlights the potential of the intervention to improve comfort inside mosquito nets. This, therefore, has a potential to increase bed net use in areas with low access to electricity.